Toward Valuing With Critical Systems Heuristics. (June 2018) - Gates, Emily F.
Evaluation is defined by its central task of valuing—the process and product of judging the merit, worth, or significance of a policy or program. However, there are no clear-cut ways to consider values and render value judgments in evaluation practice. There remains contention in the evaluation field about whether and how to make value judgments. No approach to valuing eliminates the uncertainty, plurality, and potential for conflict that comes with considering values. This article explores what critical systems heuristics (CSH), an area of applied systems thinking, might contribute to four long-standing issues regarding valuing: envisioning the social value of evaluation, framing the evaluand and evaluation, selecting and justifying criteria, and determining the roles of the evaluator(s) and stakeholders in valuing. CSH contributes concepts and tools that, in theory, support more reflective, responsible valuing although further practical application is needed.